10-minute make-up 50 step-by-step looks from fresh and natural to catwalk chic - Entrup, Boris 1978-; Hopkinson, Barbara (London Dorling Kindersley Limited, 2014)
Offers step-by-step, illustrated instructions for fifty versatile looks that can be created in only ten minutes, including detailed information on basic techniques, products, equipment, and special makeup tips and tricks. --Publisher's description.
Basics. Skincare ; Brushes and tools ; Products -- 50 looks -- Basic techniques. Foundation ; Concealer ; Blush ; Face types ; Eyes ; Pencil eyeliner ; Eyelashes ; Liquid eyeliner ; Lips ; Smoky eyes ; Eyebrows -- Beauty tips for every age -- S.O.S. tips.
Translated from German.
Keywords: Beauty, Personal; Cosmetics; Women -- Health and hygiene